Dividend Omission Announcement Effect to Market Reaction in Indonesia Stock Exchange - Mr Darmawan (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
This study examined the signalling theory about how the market / investors respond to dividend announcements made by companies listed on the Indonesia Stock Exchange during the period 2008-2012. This period was chosen because the economy and economic growth of Indonesia is relatively stable. In general, the objective of this research is to develop new theoretical approaches, in an effort to resolve the conceptual controversies regarding the impact of dividend policy on firm value. That in detail, in particular, objective: To analyze and empirically test the market reaction to the announcement dividend omissions, as well as Analyze and test empirically the firm-specific characteristics variables that affect the market reaction. The samples are all companies that announced dividend policy for 5 years as many as 242 companies with 729 event announcements. The results showed that in events dividend announcement found a significant reaction from the market. At the announcement of dividend omissions, there are 5 significant observations with 2 observations fit in theory. The study also shows none of the significant characteristics of the company is able to explain the market reaction to dividend announcements.